2017
DOI: 10.1016/j.jcms.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Cementoblastoma: An updated analysis of 258 cases reported in the literature

Abstract: Although the recurrence rate of cementoblastomas is not as high as previously believed, it is a relevant phenomenon (11.8%). The presence of bone expansion and cortical bone perforation seem to influence the recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 84 publications
2
34
0
10
Order By: Relevance
“…The present study aimed to integrate the available data published in the literature on CGCL into an updated comprehensive comparative analysis of their clinical and radiological features, as well as the frequency of recurrence. A review of pathological lesions is important because it provides information that can improve diagnostic accuracy, allowing pathologists and surgeons to make informed decisions and refine treatment plans to optimize clinical outcomes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study aimed to integrate the available data published in the literature on CGCL into an updated comprehensive comparative analysis of their clinical and radiological features, as well as the frequency of recurrence. A review of pathological lesions is important because it provides information that can improve diagnostic accuracy, allowing pathologists and surgeons to make informed decisions and refine treatment plans to optimize clinical outcomes …”
Section: Discussionmentioning
confidence: 99%
“…A review of pathological lesions is important because it provides information that can improve diagnostic accuracy, allowing pathologists and surgeons to make informed decisions and refine treatment plans to optimize clinical outcomes. [14][15][16] Most reported cases of multiple concurrent CGCLs are associated with some form of inherited syndrome or systemic disease, hence the possibility that these lesions simply represent multiple CGCLs is considered unlikely. 17 Taking into consideration the data from the study of Teixeira et al, 18 van den Berg et al 19 concluded that in almost all patients, multiple CGCLs are found mainly in those with germline mutations involving the RAS/MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to integrate the available published data on MNTI into an updated comprehensive comparative analysis of their clinical and radiological features, as well as the frequency of recurrence. A review of pathological lesions is important because it provides information that can improve diagnostic accuracy, allowing pathologists and surgeons to make informed decisions and refine treatment plans to optimize clinical outcomes [6][7][8][9][10] . This review revealed that MNTIs were slightly more prevalent in males and were markedly more prevalent in the maxilla, and most of the lesions were asymptomatic, presenting cortical bone perforation and tooth displacement.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to integrate the available data published in the literature on GSD with involvement of the jaws into an updated comprehensive analysis of their features, as well as the options of treatment and the frequency of recurrence. A review of pathological lesions and conditions is important because it provides information that can improve diagnostic accuracy, allowing pathologists and surgeons to make informed decisions and refine treatment plans to optimize clinical outcomes [12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%